Gerakan Sosial: Aksi Bela Palestina Boikot Produk Israel Di Kota Padang 2017-2023 - Rafid Sugandi; Riri Anggraini (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research aims to describe the social movement of boycotting Israeli affiliated products and its impact in Padang City, 2017-2023. The research method used is the library study method (library research). This research uses an empathetic approach to study the phenomenon of the social movement of boycotting Israeli-affiliated products in Padang city. The results of this study show that after the British issued the "Balfour Declaration" which included the establishment of a Jewish state in Palestine. From then on, Jews arrived in the Palestinian territories in very large numbers, which increased year by year. The arrival of these Jewish immigrants caused conflicts with the Palestinians because the Jewish immigrants wanted to establish a "Jewish state" in Palestine. The resistance of the Palestinian fighters continues to this day, so that the conflict continues, resulting in many casualties, especially Palestinian casualties. Israel is able to survive in Palestine because it is supported by its ally, the United States. The Palestinian-Israeli conflict has gained international attention because of the human rights violations committed by Israel. In the city of Padang, West Sumatra, Indonesia, as a form of reaction to the Israeli aggression against Palestine, there was a social movement to boycott Israeli products carried out by the government and various communities such as the Indonesian Youth National Committee (KNPI), Islamic Tarbiyah Association (PERTI) and others. The impact of the boycott social movement is the decrease in the number of consumers of Israeli affiliated product brands, namely Starbucks in the city of Padang, West Sumatra.